Qailulah in the Perspective of Islamic Neuroscience: Implications for Students' Mental and Cognitive Well-being - Azis, Annisa Rahmania; Iksan (Medina-te : Jurnal Studi Islam, 2025)
This study aims to explore the concept of Qailulah—a short midday nap encouraged in Islamic teachings—from the perspective of Islamic neuroscience, and analyze its implications for students’ mental and cognitive health. Using a qualitative literature review method, this research collected data from Islamic texts and contemporary neuroscience studies to identify overlapping insights and establish theoretical integration. A descriptive-comparative analysis was employed to examine the relevance of Qailulah to the cognitive performance and psychological well-being of students. The findings reveal that Qailulah not only holds spiritual significance in Islam but also provides scientifically measurable benefits. Neuroscientific evidence shows that short naps can enhance memory consolidation, reduce cortisol levels, improve mood regulation, and strengthen executive brain functions such as attention, emotional control, and decision-making. From an educational standpoint, Qailulah can be adopted as a holistic intervention to mitigate stress, prevent academic burnout, and enhance students’ learning efficiency. The study concludes that integrating Qailulah into modern educational practices can foster balanced student development by aligning spiritual practices with scientific understanding.